A Well-Differentiated Liposarcoma with History of Benign Prostatic: A Case Report - Hassan Tavakoli; Hadi Ahmadi Amoli; Seyed Amir Miratashi Yazdi; Mohammad Sharifi; Mina Abdolahi; Mohammad Gholizadeh (Archives of Anesthesia and Critical Care)
Liposarcoma, a malignant tumor originating from fat cells, is a rare occurrence in the retroperitoneal region. Surgical resection is the standard method for treating this cancer. This type of tumor is classified into common subtypes, which include well-differentiated liposarcoma and dedifferentiated liposarcoma. A 53-year-old male patient presented with lower left quadrant (LLQ) pain and melena for two weeks. Further diagnostic evaluation, including colonoscopy, revealed a 50 mm polyp in the hepatic flexure or distal of the ascending colon. The pathological assessment of the mass demonstrated a lipomatous lesion with a nuclear atypical lipomatous tumor, which was diagnosed as well-differentiated liposarcoma. The patient underwent surgical treatment and was discharged following his recovery. Liposarcoma, a malignant tumor originating from fat cells, is a rare occurrence in the retroperitoneal region. Surgical resection is the standard method for treating this cancer. This type of tumor is classified into common subtypes, which include well-differentiated liposarcoma and dedifferentiated liposarcoma. A 53-year-old male patient presented with lower left quadrant (LLQ) pain and melena for two weeks. Further diagnostic evaluation, including colonoscopy, revealed a 50 mm polyp in the hepatic flexure or distal of the ascending colon. The pathological assessment of the mass demonstrated a lipomatous lesion with a nuclear atypical lipomatous tumor, which was diagnosed as well-differentiated liposarcoma.